2005
DOI: 10.1021/cm050008d
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial Alignment of Polycyclic Aromatic Hydrocarbons by Solution Processing

Abstract: The self-organization of two polycyclic aromatic hydrocarbons with different aromatic core sizes, dodecylphenyl-substituted hexa-peri-hexabenzocoronene and an extended disk consisting of 96 carbon atoms 6-fold-alkyl-substituted, on the surface from solution has been investigated. Highly ordered surface layers of both materials could be obtained by the zone-casting technique, despite an apparently low self-organization in drop-cast films. The zone-cast films revealed high macroscopic uniaxial orientation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…[143] Based on this technique, the alignment of several HBC derivatives on isotropic substrates has been successfully demonstrated. [143][144][145] An optical image and high resolution (HR) TEM image from a zone-cast hexa-peri-hexabenzocoronene (HBC-C 12 ) layer are shown as examples in Figure 17b and c, respectively. From these images, it can be observed that HBC-C 12 forms aligned columnar structures along the casting direction.…”
Section: Alignment Of Organic Semiconductors Through Solution Processingmentioning
confidence: 99%
“…[143] Based on this technique, the alignment of several HBC derivatives on isotropic substrates has been successfully demonstrated. [143][144][145] An optical image and high resolution (HR) TEM image from a zone-cast hexa-peri-hexabenzocoronene (HBC-C 12 ) layer are shown as examples in Figure 17b and c, respectively. From these images, it can be observed that HBC-C 12 forms aligned columnar structures along the casting direction.…”
Section: Alignment Of Organic Semiconductors Through Solution Processingmentioning
confidence: 99%
“…In the ideal case, the columns have to bridge a gap of several micrometers between the anode and cathode, all within a defect‐free and long‐range‐ordered film. Suitable processing techniques can provide the high degree of macroscopic orientation necessary for such devices to perform well 710. Discotics can organize themselves in two different ways on surfaces, either edge‐on or face‐on.…”
Section: Introductionmentioning
confidence: 99%
“…This makes processing from solution and deposition of thin films, as required for electronic devices, difficult [92][93][94][95][96][97][98][99][100]. Attachment of solubilizing alkyl groups is then indispensable -as long as they do not obstruct the extended π-conjugation.…”
Section: Expanding Synthetic Chemistry To Complex Macromoleculesmentioning
confidence: 99%